Applied calculus : - Tan, S.T. (Thomson, 2008)
This text is appropriate for use in a two-semester or three-quarter introductory calculus course for students in the managerial, life, and social sciences. Our objective for this edition is twofold : (1) to writer an applied text that motivates students and (2) to make the book a useful tool for instructors.